The Effectiveness of Using Clay Media in Improving the Fine Motor Ability of Down Syndrome Children - Dwi Putri Sekar Harum; Mirnawati; Jiyanta (Universitas PGRI Adi Buana Surabaya, 2023)
The purpose of this study was to determine the improvement of fine motor skills through Clay media in children with Down syndrome at Yayasan Melati Anak Bangsa Martapura. The approach used in this study is a quantitative approach with the type of SSR (Single Subject Research) research. The design used in this study is A1-B-A2, for A1 is the baseline phase 1, B is the intervention phase and A2 is the baseline phase 2 The data recording technique uses direct observation using magnitude data recording. The data analysis technique used is graphic visual analysis including analysis between conditions and analysis in conditions. The subjects of this study were children with Down syndrome at Yayasan Melati Anak Bangsa Martapura with the initials HT. The results showed that there was an increase in a positive direction in fine motor skills, it can be seen from the data obtained in the baseline 1 condition, the mean level was 27%, the intervention condition the mean level was 71.3%, and the baseline condition 2 had a mean level of 88%. The result of overlap from phase A1 to B is 0% and phase B to A2 is 0%. From these data, it can be concluded that the clay media used in this study can improve the fine motor skills of children with Down syndrome at Yayasan Melati Anak Bangsa Martapura.